Thermogravimetric Experimental Study on the Co-Combustion Characteristics of Coal and Salix - Yinsheng Ma; Bao Feng; Li Gao; Zhenyu Guo; Yu Ai; Haoying Sun; Yong Zhang; Zhenyan Pan; Jingwen Mao; Ruyu Yan; Ningzhu Ye; Lei Deng (Energies)
To study the co-combustion characteristics of coal and Salix, thermogravimetric analysis is adopted to evaluate their co-combustion performance. The effect of blending ratios and synergistic are investigated in detail. Furthermore, kinetic analysis is performed. The results show that the incorporation of Salix into coal enhances combustion performance, with significant improvements observed at higher blending ratios. The ignition temperature decreases notably from 444 °C to 393 °C, highlighting an improvement in ignition properties. The primary weight loss peak shifts from 490 °C at a 15% biomass blend to approximately 320 °C at a 100% blend. Co-combustion demonstrates synergistic effects, with a 15% biomass blend optimizing combustion between 400 °C and 530 °C, while a 30% blend inhibits it. Additionally, temperatures above 600 °C exhibit an inhibitory effect. The activation energy is reduced to 25.38 kJ mol−1 at a 30% blend ratio and further to 23.06 kJ mol−1 at a 15% blend ratio at a heating rate of 30 K min−1. Increasing the biomass blend ratio and heating rate lowers the activation energy, which means facilitating the reaction process.